PANDANGAN MASYARAKAT PADA KONTEN KOMUNIKASI PARIWISATA INFLUENCER ASING: DARREN JASON WATKINS JR., (ISHOWSPEED) - Risda Dwi Pratiwi; Larasati Cahya Ramadhani (Media Bina Ilmiah, 2025)
Risda: This study examines public perceptions of tourism communication content created by foreign influencer IShowSpeed (Darren Jason Watkins Jr.) to promote tourist destinations in Indonesia. Employing a descriptive qualitative approach, the study analyzes audience responses through comments on social media platforms such as YouTube and X (Twitter). The research reveals that IShowSpeed successfully captures audience attention with an energetic and interactive approach, fostering a positive perception of Indonesian tourist destinations, particularly among young viewers. However, some critical comments arose concerning the accuracy and authenticity of the cultural representations displayed. The study concludes that foreign influencers like IShowSpeed have significant potential to enhance Indonesia's tourism image internationally through authentic, culturally sensitive communication. These findings are intended as a reference for government and tourism industries in selecting appropriate influencers for sustainable tourism promotion campaigns.